Can three‐dimensional high‐resolution anorectal manometry detect anal sphincter defects in patients with faecal incontinence?. (May 2017) - Rezaie, A.; Iriana, S.; Pimentel, M.; Murrell, Z.; Fleshner, P.; Zaghiyan, K.
Abstract: Aim: Endoanal ultrasound (EAUS) is the gold standard for detecting anal sphincter defects in patients with faecal incontinence (FI), while anorectal manometry evaluates sphincter function. Three‐dimensional high‐resolution anorectal manometry (3D HRAM) is a newer modality with the potential to assess both sphincter function and anatomy. The purpose of the present study was to compare 3D HRAM with 3D EAUS for the detection of anal sphincter defects in patients with FI. Method: A linkage analysis was performed between the 3D HRAM and 3D EAUS databases of a tertiary referral centre to identify patients with FI who underwent both 3D EAUS and 3D HRAM. With 3D HRAM, a defect was defined as any pressure measurement below 25 mmHg at rest with at least 18° of continuous expansion. The 3D HRAM findings were compared with those of 3D EAUS. Results: The study cohort included 39 patients with a mean age of 64.7 ± 15.2 years (SD); and 31 (79%) were female. Eight (21%) patients had an anal sphincter defect on EAUS with a median size of 93° (range 40°–136°). Fourteen (36%) had a defect shown by 3D HRAM with a median size of 144° (36°–180°). The sensitivity, specificity and positive and negative predictive values of 3D HRAM in detecting a sphincter defect were 75%, 74%, 43% and 92%, respectively. Conclusion: With a negative predictive value of 92%, 3D HRAM may be a useful screening method for ruling out a sphincter defect in patients with FI, thereby avoiding both EAUS and manometry in selected patients.